2004
DOI: 10.1038/sj.pcan.4500703
|View full text |Cite
|
Sign up to set email alerts
|

Computerised triage in a prostate assessment clinic

Abstract: An MS Office package has been developed to score IPSS, take a patient history, compare flows with nomograms and decide on interim management. This is based on these scores, residual volume and laboratory results. A clearly formatted GP letter is produced. The patient uses a touch screen to answer questions on the IPSS and other medical history. These questions and responses are stored in Excel spread sheets. Clinic staff then enter results of flow studies, urinalysis, U&E and PSA. Excel Visual Basic creates a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…With regard to the fact that the use of information technology is growing in healthcare system and with respect to spread of computerized triage in EDs [9,[34][35][36][37][38][39][40][41], it is suggested that another review could be performed on validity and reliability of electronic/ computerized triage. Another point is that some of triage systems [20,21,[28][29][30] are newly invented and are not used and studied enough.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the fact that the use of information technology is growing in healthcare system and with respect to spread of computerized triage in EDs [9,[34][35][36][37][38][39][40][41], it is suggested that another review could be performed on validity and reliability of electronic/ computerized triage. Another point is that some of triage systems [20,21,[28][29][30] are newly invented and are not used and studied enough.…”
Section: Resultsmentioning
confidence: 99%